Achieving more equitable access to assisted reproduction - Dyer, Silke J; Adamson, G David; Inhorn, Marcia C; Zegers-Hochschild, Fernando (BMJ (Online), 2024)
Equitable access to fertility care must be recognised as a human right so that it can be better balanced with other societal needs, say Silke Dyer, David Adamson, Marcia Inhorn, and Fernando Zegers-Hochschild